2021
DOI: 10.3389/fpsyg.2021.626750
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review Examining the Relationship Between Habit and Physical Activity Behavior in Longitudinal Studies

Abstract: Purpose: To explain physical activity behavior, social-cognitive theories were most commonly used in the past. Besides conscious processes, the approach of dual processes additionally incorporates non-conscious regulatory processes into physical activity behavior theories. Habits are one of various non-conscious variables that can influence behavior and thus play an important role in terms of behavior change. The aim of this review was to examine the relationship between habit strength and physical activity be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 76 publications
0
23
0
Order By: Relevance
“…As for habit, it has been defined as a learning sequence of acts that can result in automatic responses linked to specific cues, and has been associated with exercise behavior in health clubs (Kaushal and Rhodes, 2015;Weyland et al, 2020;Feil et al, 2021). In the PAAM model, for instance, it is suggested that the repetition of a behavior in the same context can shift the behavior gradually from explicit to implicit control processes (thus aiding habit formation), and that this shift can be supported by positive affective reactions to physical activity.…”
mentioning
confidence: 99%
“…As for habit, it has been defined as a learning sequence of acts that can result in automatic responses linked to specific cues, and has been associated with exercise behavior in health clubs (Kaushal and Rhodes, 2015;Weyland et al, 2020;Feil et al, 2021). In the PAAM model, for instance, it is suggested that the repetition of a behavior in the same context can shift the behavior gradually from explicit to implicit control processes (thus aiding habit formation), and that this shift can be supported by positive affective reactions to physical activity.…”
mentioning
confidence: 99%
“…One study concluded that building instigation rather than execution habits is related to changes in future exercise frequency (Phillips and Gardner, 2016). Positive correlations between habit strength and PA were also revealed in a current systematic review, which included longitudinal studies (Feil et al, 2021). Given the assumption that a behavior is automatically triggered by a cue, habit might contribute to exercise maintenance in that it bridges fluctuations in motivation and helps maintain the behavior even when rewards are removed (Neal et al, 2011;Rebar et al, 2019).…”
Section: Introductionmentioning
confidence: 64%
“…A strength of the study is that it examined adults in a realworld setting over a ten-week period with respect to the emergent variables of affect-based constructs and habit, which are promising for behavior change (Conner et al, 2020;Orbell and Verplanken, 2020). Only a few studies actually measured habit strength or automaticity at multiple time points (Feil et al, 2021).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…However, the moral underpinnings of offering a reward in return for health behaviors have been the subject of debate [25,26], and several studies have questioned whether HPFIs can produce sustained behavior change [27][28][29][30]. A recent paper has, however, characterized the relationship between physical activity behaviors and habits as bidirectional [31]. This means that once initiated by an HPFI [32,33], new behaviors such as activity tracking could reinforce physical activity habits and promote a virtuous cycle that persists even after the incentives have been discontinued.…”
Section: Introductionmentioning
confidence: 99%